Dialogue between Xop-T3SS effectors of Xanthomonas oryzae pv. oryzae and rice during bacterial blight pathogenesis - MONDAL, KALYAN K. (Indian Phytopathology, 2017)
Bacterial blight caused by Xanthomonas oryzae pv. oryzae (Xoo) is a major biotic threat to rice production globally. Xoo initiates dialogue with rice plant through its effectors that are secreted via type 3 secretion system (referred to as T3SS effectors). The result of this dialogue leads to the phenotype of either susceptible or resistance reaction. Xoo secrets two type of T3SS effectors, Xop (Xanthomonas outer protein) and TAL (Transcription activator like) effectors. We screened the total composition of T3SS effectors in one of the most virulent Xoo race 4 from India. Xoo race4 contains 21 Xop and 18 TAL effectors. This paper discusses our recent insight into the dialogue between Xop T3SS and rice. We studied inducible, hrp-dependent expression pattern of the Xop T3SS effectors. We created null mutants for each Xop T3SS effectors to understand their function in blight induction. Our subsequent investigation revealed that major Xop T3SS effectors like XopF, XopR plays crucial role during blight pathogenesis. The major effectors regulate the in planta Xoo growth and suppress PAMP-triggered immune (PTI) response in rice. Though there was no aberration in phenotypic as well as in vitro growth characters between wild and mutants, but mutants showed significant reduction in planta colonization relative to the wild strain. The quantitative RT-PCR analysis indicated significant fold increase in expression of the PTI marker genes in rice upon challenge-inoculation with mutants suggesting the role of effectors in suppressing rice PTI. We evident that mutants induced more callose deposition in infected rice leaves. When transiently expressed in Nicotiana benthamiana, fusion effector gene products localized to the plasma membrane. Collectively, our insight into the Xop T3SS effectors leads to the understanding that the major T3SS effectors like XopF, XopR suppress rice immune responses, and thereby favours Xoo for its in planta growth and pathogenicity during bacterial blight development.